Harvest wind energy from a vibro-impact DEG embedded into a bluff body. (1st November 2019) - Lai, Z.H.; Wang, J.L.; Zhang, C.L.; Zhang, G.Q.; Yurchenko, D.
Highlights: The DEG connected to a galloping-based vibrational system can harvest wind energy. Identification approaches for key parameters are validated through experiments. The system can operate effectively within a wide wind speed range. Adjusting stiffness and distance between DEMs can improve the system EH performance. Abstract: A novel wind energy harvester is proposed and studied in this paper. The system contains a vibro-impact (VI) dielectric elastomer generator (DEG) that can convert vibrational energy into electrical one through the impacts of a rigid ball inside. The VI DEG is embedded into a cuboid bluff body connecting to a galloping-based system. Thus, wind energy is converted to the vibrations of the bluff body, which are further harvested by the DEG. The dynamic and electrical behaviors of the proposed system under wind environments are analyzed theoretically, whereas some key parameters of the system are identified experimentally, including a wind tunnel test for the bluff body and material tests for the dielectric elastomer membrane. The dynamic and electrical outputs of the system under different wind speeds are studied through numerical simulations. The influences of the wind speed and some system parameters on the system energy harvesting (EH) performance are further discussed. Thus, the priority of the proposed system in wind EH is presented and some effective solutions to design the system and improve the system EH performance are proposed.